Contributions to the efficiency and safety of stand-alone DC microgrids (2018)
Currently, the distributed generation based on renewable energy sources is mainly DC. Those DC systems are used diverse applications such as airplanes, automobiles, ships, spaceships, computers, servers, telecommunications stations, among others. This thesis considers an isolated DC microgrid architecture composed of a renewable source, an energy storage system, and a DC load. The thesis is aimed at identifying and solving efficiency and safety problems at the source, the DC bus, and the load. During the development of this Thesis, six contributions to the state-of-the-art of DC microgrids were obtained. The first contribution is the mathematical model of a distributed maximum power point platform formed by multiple module-converter sets connected in series, which can be implemented in different programming languages and deployed on multiple platforms to evaluate optimization strategies. The second contribution is a vectorial MPPT algorithm for a distributed photovoltaic system, based in the perturb and observe algorithm. This algorithm provides a satisfactory trade-off between implementation cost and energy production since it uses a single I/V sensor. The third contribution is a reconfiguration algorithm that optimizes the electrical connections of a commercial photovoltaic array, which enables to maximize the energy extraction under arbitrary shading conditions. The fourth and fifth contributions are two control strategies, based on sliding-modes, designed for a charger/discharger DC/DC converter. Those solutions enable to regulate the voltage on the DC-bus of the microgrid to improve the microgrid safety. One of the strategies considers the current of the DC-bus into the sliding surface, which gives a better performance in terms of overshoot and settling time of the DC bus voltage. The final contribution concerns a control strategy, also based on sliding modes, to regulate a point-of-load DC/DC converter. Such a contribution enables to improve the conversion efficiency, and at the same time, to improve the load safety by reducing the current and voltage ripples delivered by the converter. Finally, those contributions improve the electrical efficiency and operational safety of DC microgrids based on renewable sources. The results obtained in this thesis were published in five journals articles and three communications to conferences. From those, three articles were published in Q1 journals, one article was published in Q3 journal, and another one was published in a Colombian journal